Automated coupling of NanoIndentation and Quantitative Energy-Dispersive Spectroscopy (NI-QEDS): A comprehensive method to disclose the micro-chemo-mechanical properties of cement pastes. (January 2018) - Wilson, William; Sorelli, Luca; Tagnit-Hamou, Arezki
Abstract: Engineering cement-based composites requires a comprehensive understanding of the microstructure features governing macroscopic properties. This work aims to foster the latest chemo-mechanical technique to disclose the micro-mechanical properties of intimately intermixed phases. Considering a typical Portland cement paste as a study case, we compared the so-far developed nanoindentation analysis methods with a new automatic method coupling Nano-Indentation and Quantitative Energy-Dispersive Spectroscopy (NI-QEDS). Besides evincing advantages and disadvantages of previous methods, the NI-QEDS analyses enabled distinguishing chemical phases having strongly overlapping mechanical properties. Results suggested the presence at the sub-micrometre scale of extra calcium, aluminum and sulfur into (or in the vicinity of) outer C–S–H. The quantitative chemistry allowed identifying the rare occurrence of nanoindentation volumes located on "pure" phases (e.g., inner C–S–H). Finally, NI-QEDS provided new knowledge on cement pastes' micro-chemo-visco-mechanical properties and showed to be a powerful tool for investigating even more heterogeneous systems.